Radicalising the Mainstream in Western Europe
XIV, 204 p. 13 illus.
Keywords: This Open Access book offers a mixed-method approach to analysing anti-Muslim narratives in interactions between the far right and the Western European mainstream. By exploring narratives that portray Islam as inherently other, the essays in this collection interrogate the effects of such narratives on the targeted group and mainstream society. Authors explore mechanisms, such as historical othering, media agenda building, and online mobilization of the far right, and harness historical analysis, media content, social media network analyses and qualitative surveys, to propose that the effects of such media narratives are far from purely symbolic. Liriam Sponholz, a media and communication scientist, is Visiting Professor at the University of Brasília (UNB) and associated researcher at the German Center for Integration and Migration (DeZIM-Institut). Her areas of research include Political Communication, Agenda Building, Social Media, Hate Speech, and Online Mobilization. Anna-Maria Meuth, a political scientist, is a Research Fellow at the at the German Center for Integration and Migration (DeZIM-Institut). Her areas of research focus include Politics and Religion, Deliberation, Local Democracy, Migration and Biopolitics. Sabrina Zajak, a political sociologist, is Professor at the University of Bochum and Head of the Department on Conflict and Consensus at the at the German Center for Integration and Migration (DeZIM-Institut). Her research focus extends from Civil Society and Social Movements to Participation and Mobilization. Mirjam Weiberg, a political scientist, is Head of Research Group on Democracy, Transfer and Policy Advice at the at the German Center for Integration and Migration (DeZIM-Institut) and writes on Religion and Politics, Fundamentalism, Democracy and Democratization, and Peace and Conflict Studies. Stefan Berger, a historian, is Professor of Social History and Director of the Institute for Social Movements at the University of Bochum, and researches the History of Social Movements, Theory of History and History of British-German Relations.